SIGNIFICANCE OF COUNSELLING ORIENTATION ON SUPERVISION OUTCOMES AMONG TRAINEE COUNSELLORS: COMPARISON BETWEEN PREVIOUS AND CURRENT STUDY IN MALAYSIA - Ghazali, N.M.; Hii, H.N.; Wan Jaafar, W.M.; Anuar, A. A.; Aden, E.; Yahyah, F. (2020)
The purpose of this study was to compare the finding of counselling orientation on supervision outcomes (satisfaction, performance and competency) among trainee counsellors on the previous and current study. The research design of this study was quantitative in nature, using survey research. The counselling orientation wasmeasured the theoretical background between trainee counsellors and their supervisor. The counsellingorientation,whichmeasuredusingSelective Theory Sorter-Revised (STS-R), the satisfaction and performance were measured by Supervision Outcomes Survey and the competency measured by Counseling Competencies Scale (CCS). The sample size for previous study was 120 respondents and the current study was 76 trainee counsellors. Therespondentswereselectedusingtheproportionatestratifiedrandomsamplingtechnique.The test analyses used were one-way analysis of variance (ANOVA) and independent samples T-test. From the result for congruence of counselling orientation was t (74) =0.46; p=0.65 (two-tailed), p>0.05. Thus, the overall results showed that the counselling orientation had no significant effect to the level of competenceofcounselortrainee(p<0.05),alignedwithConsciousCompetenceLearningTheory and Model of Dynamic Process for Supervisee Learning, where truly responsive supervision can boost supervisee learning. Insignificance of factors (frequency and theoretical orientation), with p> 0.05, contradicted with System Approach in Supervision Model (SAS) due to the difference in environmentalcontext(NorMazlinaGhazali,2015).Futureworkwillbeneededinassessingmore factorsinsupervisoryprocessforsimilarstudiestobecarriedout.Inaddition,thelocationofthe study can be varied to carry out the study using a more diverse population. Moreover, future researchersareencouragedtousealarger number of samples and expanding the sub-variables of the dependent variable and mixedmethodofdatacollectionmethodbyaddingqualitative method of interview for additional information in thestudy